Fenomena Epidemi dalam Al-Qur’an dan Hadis: Kajian Korelatif antara Wahyu dan Ilmu Pengetahuan - Fransiska, Yovia Violanda; Simbolon, Jelita; Padli, Khairul; Masyhur, Laila Sari (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2025)
Epidemics have been part of human civilization since the time of the prophets until now. Epidemics such as typhus exanthematicus or the plague experienced by the Thamud people explain that spiritual aspects can trigger the emergence of epidemics in a group. Similarly, infectious diseases such as tha'un (plague) have had a major impact on the social and religious life of Muslims since the time of the Prophet Muhammad SAW. The same is true of the Covid-19 pandemic, which has affected almost every country in the world. Therefore, this study aims to analyze how verses from the Qur'an and hadiths of the Prophet Muhammad SAW related to epidemics can be linked to modern scientific principles in combating current outbreaks. The method used by the researcher is a literature study with a historical and qualitative-descriptive approach. The results of this study show that Islam has taught the concept of epidemic prevention since the time of the Prophet through the principles of isolation, social distancing, maintaining hygiene, and treatment, which are in line with modern epidemiological principles. Thus, this study concludes that the integration of verses from the Qur'an, hadith, and modern science demonstrates the harmony between Islamic teachings and medical methods in controlling epidemics. This study confirms that Islamic teachings are not only spiritual in nature, but have also been able to provide relevant scientific solutions in dealing with epidemics, so that the adaptation of hadith in the present day remains relevant, even though it is in a different era.